Exploring mathematical pedagogical content knowledge of pre-service teachers - Edgar Sintema; Mogege Mosimege; Asvi Heris (Prometeica, 2023)
The purpose of this cross-sectional study was to examine pre-service teachers’ perceptions of their mathematical pedagogical content knowledge and to determine effect of demographic variables (Gender, year of study) on their mathematical pedagogical content knowledge. A Likert scale questionnaire was used to collect data from 104 pre-service teachers. Descriptive statistics and Mann-Whitney U-test were used to examine pre-service teachers’ perceived knowledge of teaching strategies, mathematical language and symbols, misconceptions, curriculum, and their perceived knowledge of learners. Results show that in general, majority pre-service teachers have strong perceptions of their mathematical pedagogical content knowledge. They consider lesson planning, purpose of the mathematics curriculum and assessment tools used in a mathematics classroom as important aspects of their perceived knowledge of the curriculum. It was also revealed that their perceived knowledge of misconception would enable them to know and anticipate their learners’ misconceptions. However, results also indicated that there was no statistically significant difference in pre-service teachers’ mathematical pedagogical content knowledge based on gender and year of study. Study implications are also discussed.